2021
DOI: 10.56625/jipho.v2i3.16878
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Sari Daun Kelor Melalui Air Minum Terhadap Bobot Potong, Persentae Karkas, Giblet dan Lemak Abdominal Ayam Broiler Umur 5 Minggu

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruhp emberian sari daun kelormelalui air minum terhadap bobot potong, persentase karkas, persentase giblet danpersentase lemak abdominal ayam broiler umur 5 minggu. Penelitian ini menggunakanRancangan Acak Lengkap (RAL) 4 perlakuan dan 3 ulangan, setiap unit perlakuanterdiridari 5 ekor ayam. Variabel dalam penelitian ini yaitu bobot potong, persentase karkas,persentase giblet dan persentase lemak abdominal. Data penelitian yang diperolehkemudian dianalisis secara … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…shown that the treatment of giving moringa leaf did not have a significant effect (P>0.05) on carcass percentage. In agreement with our result, Jefri et al, (2020) and Munandar (2021) did not observe differences in carcass yield at supplementation level of 20 and 60ml/l drinking water. According to Astuti and Heru (2020), the percentage of carcass is influenced by live weight and carcass weight.…”
Section: Effect Of Treatment On Carcass Percentagesupporting
confidence: 93%
See 2 more Smart Citations
“…shown that the treatment of giving moringa leaf did not have a significant effect (P>0.05) on carcass percentage. In agreement with our result, Jefri et al, (2020) and Munandar (2021) did not observe differences in carcass yield at supplementation level of 20 and 60ml/l drinking water. According to Astuti and Heru (2020), the percentage of carcass is influenced by live weight and carcass weight.…”
Section: Effect Of Treatment On Carcass Percentagesupporting
confidence: 93%
“…The potential benefit of moringa inclusion on animal production have been previously reported, such as improving productive performance and carcass quality in broiler chicken (Melesse et al, 2013). Jefri et al, (2020) reported that supplementation of moringa up to 60ml/l drinking water did not have significant effect on performance and carcass production of broiler chickens. In current study, the positive effect of moringa on final body weight was observed at supplemental level up to 120ml/l drinking water.…”
Section: Effect Of Treatment On Final Body Weight Of Broiler Chickens...mentioning
confidence: 86%
See 1 more Smart Citation